Mesenchymal stem cells repair germinal cells of seminiferous tubules of sterile rats - Tahereh Talaei; Leili Rohani; Malihezaman Monsefi; Bentolhoda Fereydouni (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Mesenchymal stem cells (MSCs) are undifferentiated cells that can differentiate and divide to other cell types. Transplantation of these cells to the different organs is used for curing various diseases. Objective: The aim of this research was whether MSCs transplantation could treat the sterile testes. Materials and Methods: In this experimental study, Donor MSCs were isolated from bone marrow of Wistar rats. The recipients were received 40 mg/kg of busulfan to stop endogenous spermatogenesis. The MSCs were injected into the left testes. Cell tracing was done by labeling the MSCs by 5-Bromo-2- Deoxy Uridine (BrdU). The immunohistochemical and morphometrical studies were performed to analysis the curing criteria. Results: The number of spermatogonia (25.38±1.57), primary spermatocytes (55.41±1.62) and spermatozoids (4.95±1.30)×106 in busulfan treated animals were decreased significantly as compared to the control group (33.35±1.78, 64.44±2.00) and (10.50±1.82)×106 respectively but stem cells therapy help the spermatogenesis begin more effective in these animals (32.78±1.99, 63.59±2.01) and (9.81±1.33)×106 respectively than the control group. The injected BrdU labeled mesenchymal stem cells differentiated to spermatogonia and spermatozoa in the seminiferous tubules of the infertile testis and also to the interstitial cells between tubules. Conclusion: We concluded that testis of host infertile rats accepted transplanted MSCs. The transplanted MSCs could differentiate into germinal cells in testicular seminiferous tubules.